2019
DOI: 10.1155/2019/9030893
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Herbal Medicine in Ameliorating Diabetic Kidney Disease via Activating Autophagy

Abstract: Diabetic kidney disease (DKD), a leading cause of end-stage renal disease (ESRD), has become a serious public health problem worldwide and lacks effective therapies due to its complex pathogenesis. Recent studies suggested defective autophagy involved in the pathogenesis and progression of DKD. Chinese herbal medicine, as an emerging option for the treatment of DKD, could improve diabetic kidney injury by activating autophagy. In this review, we briefly summarize underlying mechanisms of autophagy dysregulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…TCM holds the unique advantages of multi-target and multi-pathway regulation in the treatment of complex diseases with high e cacy, low toxicity, and few side effects [4][5][6][7][8][9] . Previous research illustrated that RJSJ is safe and well tolerated, and it does not induce body weight loss, immune dysregulation, or myelosuppression in mice 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TCM holds the unique advantages of multi-target and multi-pathway regulation in the treatment of complex diseases with high e cacy, low toxicity, and few side effects [4][5][6][7][8][9] . Previous research illustrated that RJSJ is safe and well tolerated, and it does not induce body weight loss, immune dysregulation, or myelosuppression in mice 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics and advantages of traditional Chinese medicine (TCM) in the prevention and treatment of complex diseases, such as cancers, cardiovascular diseases, infectious diseases, metabolic diseases, and neurodegenerative diseases, have attracted global attention, and such treatments have been illustrated to ameliorate symptoms, improve patient quality of life, and prolong survival [4][5][6][7][8][9] . In 2018, the WHO International Classi cation of Diseases listed traditional medicines, including TCM, in its classi cation system for the rst time 10 .…”
Section: Introductionmentioning
confidence: 99%
“…At present, a number of plant natural products have either been clinically used to treat a variety of human diseases, or have shown particularly interesting biological activities that are worth further exploration ( Li and Weng, 2017 ), such as artemisinin from artemisia annua , which has great anti-malaria effect and won the Nobel prize in 2015. Recently, some studies have found that herbal medicines play different pharmacological roles in renal diseases including ADPKD ( Wang et al, 2019 ). Several natural herbal medicines have been reported to restrain cystogenesis and improve renal function in animal models of ADPKD ( Yuajit and Chatsudthipong, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Statistics from the International Diabetes Federation show that deaths due to diabetic nephropathy account for approximately 9% of the total deaths. Hence, there is a pressing need to develop effective treatments for diabetic nephropathy patients (5). At present, the main measures used by Western medicine to treat diabetic nephropathy are to control blood sugar, blood lipids, improve renal function, adjust diet, and exercise moderately (6,7).…”
Section: Introductionmentioning
confidence: 99%